The Legal Construction of Consumer Protection in the Capital Market in the Event of a Fair Dispute Based on Law Number 21 of 2011 concerning the Financial Services Authority - Hidayati; Muhammad Adri Perwira; Andi Hakim Yunus Eka Putra (Yayasan Meira Visi Persada, 2025)
Article 33 of the 1945 Constitution is a field of the global economic life. The aim of this research is the transfer of capital investment transactions in a safe condition with the hope of obtaining profits in the future within a certain period of time. The problem is how the Legal Construction of Consumer Protection occurs in the event of a dispute based on Law Number 21 of 2011 concerning the Financial Services Authority? The method used in this research is normative juridical research, which is research focused on examining the application of rules or norms in positive law. The discussion is that the legal construction is regulated in Law No. 8 of 1995 concerning the Capital Market which has required every party to implement the principle of transparency in order to create order and efficiency and protect the interests of Business Actors. The Capital Market does not provide an exact definition of Insider Trading, but there are regulations that regulate the types of prohibited transactions, including special access in the company to conduct securities buying and selling transactions with the company. Insider trading refers to trading activities carried out by individuals that have not been announced to the public in general. In conclusion, the existence of the Financial Services Authority in Indonesia is expected to be able to maximize the existing economic activities well by realizing protection for consumers. Insider trading through illegal actions in the capital market within the company. The suggestion is that it is necessary to strengthen the institutional capacity of the Financial Services Authority through increased budgets, human resources, and information systems.